Amino acid isotopes in functional assemblages of Collembola reveal the influence of vertical resource heterogeneity and root energy supply on trophic interactions in soil food webs. (November 2022) - Li, Zhipeng; Bluhm, Sarah L.; Scheu, Stefan; Pollierer, Melanie M.
Abstract: The vertical heterogeneity of trophic interactions in soil food webs in temperate forest systems and its response to deprivation of root energy supply are poorly understood. In the present study, community-level trophic niches of Collembola functional groups (epedaphic, hemiedaphic and euedaphic) were analyzed using compound specific isotope analysis (CSIA) of carbon (C) and nitrogen (N) in amino acids (AAs) in a root-trenching experiment. The δ 15 N values of phenylalanine, serving as proxy for N resources, were higher in euedaphic Collembola than in ep-/hemiedaphic Collembola, suggesting that euedaphic Collembola mainly utilized N from processed organic substrate in deeper soil, while leaf litter was the dominant N source for ep-/hemiedaphic Collembola. The trophic position calculated from CSIA (TPCSIA ) of euedaphic Collembola was higher than that of epedaphic Collembola in most of the studied forest sites, reflecting a higher number of trophic transfers in the soil than in the litter layer. For the first time, we found evidence that the deprivation of root energy supply can decrease the TPCSIA of soil omnivores, suggesting that root-derived C may increase the number of trophic transfers and food chain length in soil food webs. However, effects varied among functional groups of Collembola in different forest stands, indicating that the association between root energy supply and trophic interactions is only partially in line with the 'productivity hypothesis' and strongly mediated by vertical resource heterogeneity, regional conditions and feeding strategies of consumers. Finally, our results are in line with recent studies, suggesting that saprotrophic microorganisms, especially saprotrophic fungi, are the predominant resources for Collembola, whereas the contribution of mycorrhizal fungi and plants is subordinate. Overall, by using CSIA of AAs our study provides novel information on trophic niches of microarthropods in forest soils, extending our understanding of the influences of vertical resource heterogeneity and root energy supply on trophic interactions in soil food webs. Highlights: Trophic niches of Collembola were investigated using isotope analyses of amino acids. Trophic position of Collembola functional assemblages increases with soil depth. Root-derived resources are considered in the context of the 'productivity hypothesis'. Deprivation of root-derived resources can decrease Collembola trophic position. Saprotrophic microorganisms are the major food source for Collembola.